Rozwój gospodarczy Niemieckiej Republiki Demokratycznej w jej dwudziespopięcioleciu - Jurek, Wacław (Wydział Prawa i Administracji UAM, 1975)
The author has shown the changes in the economic development and economy structure in the GDR. Part I contains the conditions of the beginning of development; part II shows us the principle changes in the structure of GDR economy; part III concerns the demographic situation and the last part deals with the role of external trade in the GDR economy.
The Latest Institutional Transformations in the German Democratic Republic